Experimental modeling of atmospheric discharge phenomena and charged dust particle interactions - Abdelaal, Mohamad E.; Dokuchaev, Igor. V.; Malinovskaya, Elena A.; Klimov, Stanislav I.; Dolnikov, Genady G.; Zakharov, Alexander V. (Frontiers in Astronomy and Space Sciences, 2024)
The upper atmosphere, comprising the mesosphere and thermosphere, is intricately influenced by various atmospheric and magnetospheric impacts. Various atmospheric waves excited in the troposphere can propagate into the mesosphere-thermosphere (M-T) region, altering its dynamics. Additionally, large-scale disturbances in the middle atmosphere, such as sudden stratospheric warming and geomagnetic disturbances induced by solar activity, affect the upper atmosphere. To better understand these complex processes, observations from multiple platforms and instruments, along with modeling studies, are necessary. This study presents experimental investigations into the electromagnetic signatures generated by atmospheric discharge conditions, including breakdown events and interactions of charged dust particles. A vacuum chamber was used to simulate upper atmospheric conditions. An electromagnetic signal analyzer (EMA) registered signals generated from the atmospheric discharge and the electromagnetic signature of charged dust particles. The results provide crucial insights into the distinctive electromagnetic processes occurring during breakdown events and charged particle interactions within Earth's atmosphere.